Gender differences in skilled performance under failure competitive environments: evidence from elite archers - Li, Chunhua; Zhao, Yangqing (Frontiers in Psychology, 2024)
This study explores the gender differences in archers' ability to cope with adversity, highlighting the significant cold-hand effect observed in both male and female archers, with notable differences in the last arrow performance under pressure. Using data from professional recurve archery competitions held between 2012 and 2021, the Poisson regression analysis reveals that male and female archers' performance dropped significantly after experiencing two consecutive missing bullseyes, which means a cold-hand effect exists. However, although there was no significant difference in the performance of male and female archers on the third arrow, female archers have significantly lower last arrow per set scores than male archers after near poor performance or being in a situation where losing can only be avoided by winning the current set. This finding suggests that female archers are more vulnerable to the potentially negative effects of adversity caused by trailing or recent failures than their male counterparts. In addition, the reason for such a gender gap has been discussed.